On the role of polydispersity on the phase diagram of colloidal rods. Issue 9 (9th February 2023) - De Filippo, Carlo Andrea; Del Galdo, Sara; Corsi, Pietro; De Michele, Cristiano; Capone, Barbara
Abstract : We here report on the unexpected role of diameter polydispersity on the phase diagram of diameter- and length-polydisperse hard spherocylinders: a theoretical and computational study. Abstract : The rich and complex phase diagram typical of anisotropic biological or synthetic nanoparticles, has brought a great deal of interest over the equilibrium phase behaviour of non-spherical colloids. Amongst the class of anisotropic nanoparticles, hard spherocylindrical colloids have been, over the years, extensively studied because of their optical properties, for their rich phase diagrams, and their important industrial applications, as model particles for biological systems (viruses), or for example as potential drug carriers having the ability of surviving the attacks of the immune systems. As real anisotropic nanoparticles are often polydisperse in size and/or in shape, unveiling the effect of such a perturbation over their equilibrium phase diagram is of paramount importance. This work focuses on the effects of polydispersity over the full equilibrium phase diagram of hard spherocylindrical colloids (HSCs). Previous studies showed that a polydispersity in L alters the equilibrium phase diagram of HSCs. With this work we determine, both theoretically as well as computationally, the effects due to a generic polydispersity, namely in D, in L and, in both ones, on the equilibrium phase diagram and introduce a viable theoretical generalisation of the Onsager theory that allows us to get some insight into the observed phase behaviour.